Early second-trimester plasma levels of NT-proBNP in women who subsequently develop early-onset preeclampsia. (17th September 2017) - Junus, Katja; Wikström, Anna-Karin; Larsson, Anders; Olovsson, Matts
Abstract: Plasma levels of NT-proBNP are elevated in women with preeclampsia at the time of diagnosis. The objective of this case-control study was to evaluate N-terminal proBNP (NT-proBNP) in maternal plasma as an early second-trimester biomarker for prediction of early-onset preeclampsia. In early second-trimester samples, women who later developed preeclampsia at gestational age 34 wk + 0 or earlier ( n  = 16) had similar plasma levels of NT-proBNP (median 51.8, range 26.1–131.9 pg/ml) as women with uncomplicated pregnancy outcomes ( n  = 43) (53.0, 14.9–184.2 pg/ml). The early second-trimester level of NT-proBNP cannot therefore be used as a predictive biomarker of early-onset preeclampsia.